The effects of transient receptor potential cation channel inhibition by BI 1358894 on cortico-limbic brain reactivity to negative emotional stimuli in major depressive disorder - Grimm, Simone; Keicher, Christian; Paret, Christian; Niedtfeld, Inga; Beckmann, Christian; Mennes, Maarten; Just, Stefan; Sharma, Vikas; Fuertig, René; Herich, Lena; Mack, Salome; Thamer, Claus; et al. (European neuropsychopharmacology, 2022)
Abnormal emotional processing in major depressive disorder (MDD) has been associated with increased activation to negative stimuli in cortico-limbic brain regions. The authors investigated whether treatment with BI 1358894, a small-molecule inhibitor of the transient receptor potential cation channel subfamily C leads to attenuated activity in these areas in MDD patients. 73 MDD patients were randomized to receive a single oral dose of BI 1358894 (100 mg), citalopram (20 mg), or matching placebo. Brain responses to emotional faces and scenes were investigated using functional magnetic resonance imaging. Primary endpoints were BOLD signal changes in response to negative faces in cortico-limbic brain regions, i.e. bilateral amygdala (AMY), dorsolateral prefrontal cortex, anterior insula (AI), and anterior cingulate cortex. Secondary endpoints were BOLD signal changes in response to negative scenes. For each region, separate ANOVA models were computed for the comparison of treatments (BI 1358894 or citalopram) vs. placebo. The adjusted treatment differences in the % BOLD signal changes in the faces task showed that BI 1358894 induced signal reduction in bilateral AMY and left AI. In the scenes task, BI 1358894 demonstrated significant signal reduction in bilateral AMY, AI, anterior cingulate cortex and left dorsolateral prefrontal cortex. Citalopram failed to induce any significant reductions in BOLD signal in both tasks. BI 1358894-mediated inhibition of the transient receptor potential cation channel subfamily resulted in strong signal reduction in cortico-limbic brain regions, thereby supporting development of this mechanism of action for MDD patients.
Online verfügbar: 4 November 2022, Artikelversion: 4 November 2022
Gesehen am 06.06.2023